2010
DOI: 10.1590/s0100-879x2010007500007
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord blood cells in infarcted rats

Abstract: 90° and reduced shortening fraction (less than 50%). In addition, cardiac indexes of left ventricular contractility and relaxation were 5484 ± 875 and -4032 ± 643 mmHg (cryopreserved hUCB) and 4585 ± 955 and -2862 ± 590 mmHg (fresh hUCB), respectively. These values were not statistically different from those of saline-treated animals. Cardiopulmonary exercise test profile was typical of infarcted hearts; exercise time was about 14 min and maximal VO2 was 24.77 ± 5.00 mL·kg-1·min-1. These data show that hUCB th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Preclinical studies with UCB cells have demonstrated their efficacy in various diseases, such as heatstroke, amyotrophic lateral sclerosis, post-infarct cardiac regeneration, and liver diseases [ 4 , 7 - 11 ]. Subsequently, multiple groups have demonstrated that the delivery of UCB cells has the potential to improve cardiac function in animals following acute myocardial infarction (MI) in the left ventricle [ 12 - 14 ]. Recent studies in a novel sheep model of chronic right ventricular volume overload showed that UCB cells transplanted in the right ventricle improved heart function [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies with UCB cells have demonstrated their efficacy in various diseases, such as heatstroke, amyotrophic lateral sclerosis, post-infarct cardiac regeneration, and liver diseases [ 4 , 7 - 11 ]. Subsequently, multiple groups have demonstrated that the delivery of UCB cells has the potential to improve cardiac function in animals following acute myocardial infarction (MI) in the left ventricle [ 12 - 14 ]. Recent studies in a novel sheep model of chronic right ventricular volume overload showed that UCB cells transplanted in the right ventricle improved heart function [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This direct administration of cells into the damage heart muscle has proven to be more effective than indirect methods. Comparing indirect and direct delivery methods, intramyocardial injection significantly reduced the infarct size area as compared to indirect methods of HUCB cell delivery [110]. Although this method is preferred, there are some disadvantages that need to be taken into consideration before delivering the cells.…”
Section: Intramyocardial Injectionmentioning
confidence: 99%
“…Studies that are more recent further support the intramyocardial injection as an effective cell delivery system. HUCB cells were injected into one or two positions of the myocardium near the edge of the infarct area in rats [110]. Three weeks after implantation, HUCB cells were detected using nuclear staining primarily in the border of the infarct area, suggesting that the cells have the potential to survive for at least three weeks following implantation.…”
Section: Intramyocardial Injectionmentioning
confidence: 99%
“…UCB cells have been standardized therapeutic agents in patients suffering from major hematological disorders since 1988 [13]. Subsequently, multiple groups have been pioneering human umbilical cord blood-derived mononuclear cells (UCB-MNCs) in preclinical experimental approaches for myocardial repair and regeneration [14][15][16][17][18][19]. Collectively, these studies suggest a cellmediated improvement in the ejection fraction, wall motion, and cardiac contraction, along with a lowered left ventricular end-diastolic pressure.…”
Section: Introductionmentioning
confidence: 99%